Anti‐inflammatory Activities of Eleven Centaurea Species Occurring in the Carpathian Basin. (4th June 2012) - Csupor, Dezső; Widowitz, Ute; Blazsó, Gábor; Laczkó‐Zöld, Eszter; Tatsimo, Joel S. N.; Balogh, Ágnes; Boros, Klára; Dankó, Balázs; Bauer, Rudolf; Hohmann, Judit
<x xml:space="preserve">Abstract</x> Our study aimed at the identification of anti‐inflammatory activities of different fractions of C. sadleriana extract after per os administration in rats, the identification of the active compounds of the plant and the investigation of the in vitro anti‐inflammatory activities of Centaurea species native to or cultivated in the Carpathian Basin. The aerial parts of Centaurea sadleriana Janka have been used in Hungarian folk medicine to treat the wounds of sheep. Methanol extract of C. sadleriana was fractioned by solvent‐solvent partitioning. The n‐hexane fraction was further fractionated and the anti‐inflammatory activities of certain subfractions were confirmed in vivo in rats. The n‐hexane and chloroform fraction of the methanol extract of C. sadleriana exhibited remarkable COX‐1 and COX‐2 inhibiting effects in vitro. Chromatographic separation of the fractions led to the identification of the active subfractions and 11 compounds (α‐linolenic acid, γ‐linolenic acid, stigmasterol, β‐sitosterol, campesterol, vanillin, pectolinarigenin, salvigenin, hispidulin, chrysoeriol and apigenin). The in vitro screening for anti‐inflammatory activities of further Centaurea species occurring in the Carpathian Basin (C. adjarica, C. bracteata, C. cataonica, C. cynaroides, C. dealbata, C. indurata, C. macrocephala, C. melitensis, C. nigrescens, C. ruthenica) revealed considerable COX‐1 and COX‐2 inhibitory activities. Because C. sadleriana is an endangered species native only to the Carpathian Basin, the investigation of more prevalent species is reasonable. Copyright © 2012 John Wiley & Sons, Ltd.